Exploring substance use and mental health for minority transgender youth: Implications for advanced practice nurses. Issue 3 (March 2020) - Raynor, Phyllis A.; Nation, Austin; Outlaw, Freida
ABSTRACT: Background: Transgender youth, particularly if they are transgender female and of a minority racial or ethnic group (i.e., minority transgender youth [MTY]), are known to have higher incidence of new HIV infections, substance abuse, and suicidality when compared with cisgender youth. Mental health disparities and substance use among MTY, between the ages of 13–24 years, have been underexplored in the United States, although they have serious public health concerns contributing to morbidity and mortality. Objectives: To examine the US literature to discover what is known about the intersection of substance use, mental health disorders, and associated health risks for MTY. Data sources: An integrative review exploring experimental and nonexperimental research was conducted from 2010 to 2018 using Cumulative Index for Nursing and Allied Health (CINAHL), PsycINFO, and PubMed. Articles were selected if the research identified MTY, mental health and/or substance use risks, data-driven outcomes, or considerations that could potentially influence MTY outcomes. Ten articles were included in the final selection. Conclusions: All studies addressed mental health, substance use, and/or health risks, although many of the articles explored all transgender youth outcomes without a particular focus on MTY. Identified factors linked to poor health outcomes included socioeconomic vulnerability, substance use, mood disorders, self-harm, and risky sexual behaviors. Implications for practice: The authors have provided recommendations regarding culturally appropriate, compassionate, evidence-informed practices for engaging MTY and their families to promote greater well-being for all youth, regardless of gender identity.